Evaluation of the Egyptian agricultural development during the Mamluk era - Yaakub, Noor Inayah; Mujani, Wan Kamal; Wan Hussain, Wan Mohd Hirwani; Zainol, Zinatul Ashiqin; Mohamad, Mohd Nasran; Jamsari, Ezad Azraai; Jusoff, Kamaruzaman; Sulaiman @ Mohamad, Adibah (IDOSI Publications, 2011)
This article evaluates the agriculture development in Egypt during the Mamluk era. This study shows that there are several factors that affected agriculture and its produce, such as the problems in the iqta' system, the problems in the irrigation system, the shortage of a productive labour force for the land, the lack of technological innovation in agriculture and the disturbances caused by climatic and biological disasters. However, these factors did not lead to a total decline and absolute collapse of the Mamluk agriculture era.